Perilaku Spasial Penduduk Kecamatan Setiabudi Dalam Memilih Lokasi Belanja Kebutuhan Primer - Irfan Maulana (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2022)
It is well acknowledged that Setiabudi district dominates the market in South Jakarta. Based on the quality of service, market in general is classified into either traditional or modern market. As a matter of fact, every people have their own distinctive behaviour in making a decision, especially in choosing where to shop for their primary needs. The primary needs taken as the object of this research are food and clothing. The objective of this research is to analyse the spatial behaviour of Setiabudi district communities in choosing where to shop for their primary needs based on the characteristics of behaviour (cognitive, affective, conative) and shopping location. In this research, the data collection technique used is an in-depth interview with informants and the analysis methods used are spatial and qualitative analysis. The result of this research shows that, in deciding where to shop for their daily needs of food preparation, most of the population tend to choose the traditional market as their shopping location, because of the affective factor where they feel that the destined shopping location is closer to their residential area or near to their workplace. Meanwhile, in deciding where to shop for clothing, most of the population tend to choose the modern market as their shopping location, because of the affective factor where they feel comfortable with the choice and quality of the clothing in the destined shopping location.